Compassionate Love Scale: Validity and Reliability Study - Abdurrahman KILIÇ; Şeyma ŞAHİN; Burcu ÖKMEN (Değerler Eğitimi Dergisi)
In this research, it is aimed to develop a valid and reliable scale that measures the compassionate love perceptions of individuals. After exploratory factor analysis, a scale consisting of 26 items was formed under six factors. It was found that these 26 items explained 63.958% of the total variance. The factors’ names are: 1) Compassionate Love and its Function, 2) Compassionate Love and Behaviors, 3) Compassionate Love and Values, 4) Compassionate Love and Its Source, 5) Compassionate Love and Personal Traits, and 6) Compassionate Love and Differences. As a result of the confirmatory factor analysis, it was determined that the X2/df value was 2.53, the RMSEA value was 0.067, the NFI value was 0.93, the CFI value was 0.95, the GFI value was 0.86, and the AGFI value was 0.83. In the reliability study, the Cronbach's Alpha value of the whole scale was found to be 0.88. In the test-retest reliability, the correlation value between the two tests was found to be 0.78. When all the results of the validity and reliability studies of the scale are examined, it is thought that the scale is a valid and reliable measurement tool that can measure the compassionate love perceptions of individuals.